Comparing the Effects of Thyme (Zataria multiflora) and Rosemary (Rosmarinus officinalis) Essential Oils on Microbiological, Physicochemical, and Sensory Properties of Vacuum-Packaged and Refrigerated Chicken Breast - Sahar Piruz; Mohammadreza Khani (Journal of Food Quality)
This study aimed to compare the effects of thyme and rosemary essential oils (EOs) with vacuum packaging on shelf life extension and organoleptic properties of chicken breast meat. For this purpose, two concentrations of 0.1% and 0.3% (v/w) from thyme and rosemary EOs were added individually to fresh chicken breast samples, packed under vacuum conditions, and stored at 4°C for 12 days. All the samples were evaluated for microbiological, physicochemical, and sensory properties at 3-day intervals. The results showed that the thyme EO treatments, especially at 0.3% concentration, significantly reduced both total and psychrotrophic colony counts, and they were more effective in reducing microbial counts compared to rosemary EO treatments. Moreover, thyme EO significantly controlled Escherichia coli growth in treated samples. TBA values in treated samples with thyme EOs were significantly less than in rosemary EOs and control samples. Results indicated that rosemary EO treatments had the lowest pH during 12 days. Colorimetric and organoleptic analysis of the samples showed statistical differences on various days. In the EOs-treated chicken breasts, the color and texture of the samples improved compared to controls, but the taste and odor were not desired at the higher concentration of thyme and rosemary EOs.